A Delicate Balance: Global Perspectives on Innovation and Tradition in the History of Mathematics : A Festschrift in Honor of Joseph W. Dauben - Rowe, David E.; Horng, Wann-Sheng (Trends in the History of Science,, 2015)
Joseph W. Dauben, a leading authority on the history of mathematics in Europe, China, and North America, has played a pivotal role in promoting international scholarship over the last forty years. This Festschrift volume, showcasing recent historical research by leading experts on three continents, offers a global perspective on important themes in this field.